Analisis Konservasi Energi Gas Suar Bakar Pada PT. Arun NGL - Erwin Ash'ari; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
One of the major issues facing the world today is global warming. This problem is caused by the increasing concentration of carbon dioxide and other greenhouse gases in the atmosphere. A suggested method for controlling the level of greenhouse gases in the atmosphere is the prevention of burning flaring gas unit. In this study, two methods are proposed to conserve flaring gas at liquefied natural gas refineries PT. Arun. This method aims to minimize the environmental and economic losses of flaring gas combustion. The proposed method are: 1) utilization of flared gas as fuel for gas turbine power generation and 2) compression and injection of boiled gas into the refinery pipe. Determination of the most suitable methods and tools required for the two methods was done by means of simulation. The simulation was designed to determine the potential power generation and compression power required. The results demonstrate that the use of flared gas as fuel can generate 2130 MW of electricity while requires a compressor with a maximum pressure of 129 bar to inject the flaring gas into the refinery pipe. Study of economic analyzes for both methods was also conducted. From the analysis, it is found that compression of gas into the pipeline requires a lower capital cost than if the gas is utilized as gas turbine fuel. Therefore, the gas injection into the refinery pipe is a suitable alternative to prevent adverse environmental impacts through large amounts of carbon dioxide emissions in the atmosphere due to flaring gas burning.